PREVENTION OF GASTROPROTECTIVE ACTIVITY OF CHINESE BETEL EXTRACT (PEPEROMIA PELLUCIDA L.) ON THE HISTOPATHOLOGICAL FEATURES OF THE STOMACH IN A MOUSE MODEL OF GASTROENTERITIS - Savitri, Lisa; Prasetyawan, Fendy; Saristiana, Yuneka; Juwita, Syntia Tanu; Amanda, Cornelia; Mebung, Konradus Klala (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Gastroenteritis is a common gastrointestinal disorder characterized by inflammation of the stomach and small intestine, often leading to symptoms such as diarrhea, vomit-ing, and abdominal pain. This study investigates the gastroprotective effects of Pepe-romia pellucida (Chinese betel) extract on histopathological features of the stomach in a mouse model of gastroenteritis. Male Swiss strain mice, aged 2-3 months, were treated with different doses of P. pellucida extract (100, 300, and 500 mg/kg BW) for 7 days after inducing gastroenteritis with Escherichia coli infection. Histopathological ex-amination showed that the extract significantly reduced cell degeneration, necrosis, and polymorphonuclear leukocyte infiltration in the stomach compared to the negative control group. The highest dose (500 mg/kg BW) exhibited the most prominent gastro-protective effect. These results suggest that P. pellucida possesses promising thera-peutic potential for gastroenteritis, possibly due to its bioactive compounds such as flavonoids, tannins, and saponins. Further studies are needed to explore the underly-ing mechanisms and optimize its therapeutic application.